Neonatal paroxetine withdrawal syndrome. Issue 2 (1st March 2001) - Stiskal, J A; Kulin, N; Koren, G; Ho, T; Ito, S
Abstract : Four term neonates presented with symptoms such as jitteriness and necrotising enterocolitis after paroxetine exposure in utero.